Carte Reduite Des Parties Septentrionales Du Globe, Situées, Entre L'Asie Et L'Amerique Pour server a l'Histoire Generale des Voyages Par M. Bellin Ingr. De la Marine 1758 - Bellin, Jacques Nicolas, 1703-1772 (Bellin, Jacques Nicolas, 1703-1772, 1758)
18th century Copper engraving. Relief shown pictorially. Printed in center of top in cartouche: "Carte Reduite Des Parties Septentrionales Du Globe, Situées, Entre L'Asie Et L'Amerique Pour server a l'Histoire Generale des Voyages Par M. Bellin Ingr. De la Marine 1758." Printed beneath bottom border on left: "Tome XV." Printed beneath bottom border on right: "No. 4." Written in pencil in bottom right corner: "1759. 410." Depicts the northeast Asia including the Kamschatka Peninsula in Russia and Canada or northern North America with much of the northwestern area of North America left blank and labeled as "Tout ceci est inconnu." Includes notes on exploration and discovery throughout including notes on the alleged exploration of Admiral de Fonte, Juan de Fuca, and Martin d'Aguilar. Also includes notes on land found by the Russians including Alexei Chirikov and land discovered by Juan de Gama. Shows various mythical areas including the Sea of the West and Quivira. Also marks the alleged entrance to the sea, supposedly found by Juan de Fuca in 1692 and Martin d'Aguilar in 1603. Detail is greatest around Hudson's Bay and Labrador. Printed beneath the cartouche is a note stating that it is unknown whether the area between North America and Asia is land or sea. Includes strong rhumb lines from the points in North America and Asia. Prime Meridian: Paris. Scale: c.a. 1:25,000,000. Jacques Nicolas Bellin (1703-72) was the French Royal Hydrographer. Among his works are Charlevoix's "Nouvelle France" (1744), "Hdyrographique Francois" (1756-65), "Petit Atlas Francais" (1763) and Atlas de Corse (1769) (Tooley, 49). Source(s): National Maritime Museum. Online Catalog. Accessed 18 May 2009. Tooley, Ronald Vere. "Tooley's Dictionary of Mapmakers." Hertfordshire: Map Collector Publications Limited, 1979.